Teachers become cocreators through participation in a teacher professional development (TPD) course in a resource constraint environment in South Africa. Issue 1 (21st December 2017) - Botha, Adele; Herselman, Marlien
Abstract: The purpose of this paper is to provide insight into how teachers became cocreators by merging their existing knowledge of their subject, context, and new knowledge of using mobile tablets towards enhancing their teaching practices. This was achieved in a specific area in the Eastern Cape Province of South Africa over a period of 3 years. The intentional situating of teachers as cocreators was implementation through a teacher professional development (TPD) course. The course consisted of 10 modules presented and completed over a 1‐year period. The TPD course was developed as an artefact using Design Science as a methodology with 3 iterations of implementation to refine it. The development of the course and its iterative implementation and refinement was grounded in the Living Lab open innovation approach with elements of gamification (coopetition), and various stakeholders were incorporated. Structuration theory was applied to indicate the "duality of structure" where structure and agency are related and dependent on each other and agents' actions produce, reproduce, and develop social structures. Technology endowments were integrated as part of the gamification and were dependent on predefined cocreation events. Each event was linked to a badge, and teachers had to provide practice‐based evidence of how new knowledge, proficiencies, and skills gained during the TPD sessions was adapted to their own subject and context knowledge and practically implemented in their classrooms. This presents an innovative way to introduce and use tablets in teaching and learning (structure) as teachers (agents) are acknowledged as domain and subject experts, and through exposure to technology and pedagogical strategies in using the technology (resources), they become cocreators of their own new enhanced classroom practice (social structures) and adopted the technology.